2008
DOI: 10.1080/15487760701853326
|View full text |Cite
|
Sign up to set email alerts
|

Supported Employment for Middle-Aged and Older People with Schizophrenia

Abstract: Many middle-aged and older people with severe mental illness are interested in working or volunteering. However, very few vocational rehabilitation programs target older clients with psychiatric illness. We examined employment outcomes among 50 middle-aged and older participants with schizophrenia or schizoaffective disorder in a 12-month randomized controlled trial comparing two work rehabilitation programs: Individual Placement and Support (IPS; a supported employment model) and conventional vocational rehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 17 publications
1
58
0
3
Order By: Relevance
“…In particular, clients who had a prior work history of one or more years were more likely to benefit from SE (Cook 2007;Cook and O'Day 2006;Danley et al 1992;McGurk and Mueser 2006a;McGurk et al 2003). Clients who worked more recently were also more likely to attain competitive employment (Regenold et al 1999;Twamley et al 2008). A study that combined data from 4 RCTs found that amongst IPS clients, work history was the only significant predictor for job acquisition.…”
Section: Intrinsic Characteristicsmentioning
confidence: 99%
“…In particular, clients who had a prior work history of one or more years were more likely to benefit from SE (Cook 2007;Cook and O'Day 2006;Danley et al 1992;McGurk and Mueser 2006a;McGurk et al 2003). Clients who worked more recently were also more likely to attain competitive employment (Regenold et al 1999;Twamley et al 2008). A study that combined data from 4 RCTs found that amongst IPS clients, work history was the only significant predictor for job acquisition.…”
Section: Intrinsic Characteristicsmentioning
confidence: 99%
“…The median follow-up period was 18 months (range = 12 to 120 months). The client population varied greatly across the cohorts, including people with co-occurring disorders (Bush et al, 2009;Xie et al, 2010;McHugo et al, 2012), people early in the course of illness (Drake et al, 2013), people with severe mental illness over 45 years of age (Twamley et al, 2008), and people with significant illness-related impairments in functioning (i.e., severe mental illness) (Mueser et al, 1997;Lam and Rosenheck, 2000;Torrey et al, 2000;Bond et al, 2001;Twamley et al, 2008;Burns et al, 2009;Xie et al, 2010;Kilian et al, 2012;Kukla et al, 2012;McHugo et al, 2012). Participants were recruited from community mental health centers in the US (Mueser et al, 1997;Torrey et al, 2000;Bond et al, 2001;Twamley et al, 2008;Bush et al, 2009;Xie et al, 2010;Kukla et al, 2012;McHugo et al, 2012) and abroad (Burns et al, 2009;Kilian et al, 2012), emergency departments (Drake et al, 2013), as well as emergency shelters, outdoors, and public or abandoned buildings (Lam and Rosenheck, 2000).…”
Section: Study Selectionmentioning
confidence: 99%
“…Clinical trials have shown IPS to be associated with higher CE rates, shorter time to entering CE, greater numbers of hours worked per week, and more weeks worked per year among individuals diagnosed with SMI [13,[16][17][18][19][20][21][22][23][24][25][26] and, most recently, among veterans with posttraumatic stress disorder (PTSD) [27]. The program is most effective when fidelity to the model is high [28][29][30].…”
Section: Supported Employmentmentioning
confidence: 99%